The Protective Effects of Lipid-Lowering Agents on Cardiovascular Disease and Mortality in Maintenance Dialysis Patients: Propensity Score Analysis of a Population-Based Cohort Study - Tsai, Ming-Hsien; Chen, Mingchih; Huang, Yen-Chun; Liou, Hung-Hsiang; Fang, Yu-Wei (Frontiers in Pharmacology, 2022)
Lipid-lowering agents display limited benefits in cardiovascular disease and mortality in patients undergoing dialysis. Therefore, lipid-lowering agents are not routinely recommended for dialysis patients. The aim of this study is to assess the effects of lipid-lowering agents on clinical outcomes in dialysis patients on the basis of real-world evidence. This research used Taiwan National Health Insurance Research Database to identify dialysis patients from January 2009 to December 2015 were selected and divided into a case group treated with lipid-lowering agents (n = 3,933) and a control group without lipid-lowering agents (n = 24,267). Patients were matched by age, gender, and comorbidities in a 1:1 ratio. This study used a Cox regression model to estimate the hazard ratios (HR) for mortality and major adverse cardiovascular events (MACEs) for events recorded until December 2017. During a mean follow-up time of about 3.1 years, 1726 (43.9%, incidence 0.123/person-year [PY]) deaths and 598 (15.2%, incidence 0.047/PY) MACEs occurred in the case group and 2031 (51.6%, incidence 0.153/PY) deaths and 649 (16.5% incidence 0.055/PY) MACEs occurred in the control group. In the analysis of Cox regression model, lipid-lowering agent users showed a significantly lower risk of death (HR:0.80; 95% confidence interval [CI]: 0.75–0.85) and MACEs (HR:0.85;95%CI: 0.76–0.95) compared with lipid-lowering agent nonusers. Moreover, the survival benefit of lipid-lowering agents was significant across most subgroups. Dialysis patients treated with lipid-lowering agents display a 20% and 15% reduction in their risk of mortality and MACEs, respectively.